A mediação pedagógica na inclusão da criança com autismo na educação infantil - Chiote, Fernanda de Araújo Binatti (2011)
The paper aims at analyzing the role of the pedagogical mediation in the inclusion of children with autism, being the mediation a process of meaning and constitution of that child within children’s education, favoring the appropriation of cultural practices historically delimited in that space, in the development of a self-conscience and the others. It was made a study case in a Municipal Center of Children’s Education in the district of Cariacica (CMEI), state of Espírito Santo, having as subjects the autistic child, the teachers and the other children in class. The historical-cultural perspective constituted the theoretical and methodological basis, represented by Vigostki studies (1983, 1997) and other authors who share the same referential and consider that the subjects are constituted and develop in the concrete life conditions, through relations and interactions that are made possible for them, giving relevance to the other’s role and the language in processes mediated. Data were collected through the participant observation, interviews and documental analyses, with field diary record, videotapes and photos. The organization and data analyses were supported by micro genetics approach in the search of revealing the processes of development. The teachers’ acting in the beginning of the study was linked to the conceptions they had concerning autism, based on the incapacity and limitation of the child. The analyses indicate that the change of look regarding the autistic child, noticing him/her as subject, as well as their ways to notice themselves as teachers of an autistic child in the children’s education were being constituted as there was a movement to insert that child in his/her group in order to make him/her realize and organize through the collective experience in different time and space of the CMEI. The pedagogical mediations are constituted in a process to guide the actions of the autistic child to what was expected from him/her (and the other children) in a certain situation, in a doing for/with him/her, favoring, by orientation, the regulation of the other. The investment of the adult in the participation of such child, as subject of/in the school/cultural practices, broke with his/her isolation and enabled the construction of a new image, to whom can learn with the other. That new image got the children of the group closer with the autistic one, what favored the magnification of the typically childish experiences, like playing, in relation with their pairs and not only with the adult. Our reflections show that in the space of children’s education the pedagogical mediation may favor the development of the autistic child, allowing him/her appropriations and sharing of the broadest and most complex senses regarding the physical and social environment and him/herself in this context.